Dorsal Root Ganglion Pulsed Radiofrequency with Scar Radiofrequency Ablation Combined for Chronic Postoperative Abdominal Pain: A Retrospective Study - Gu R; Huang Y; Li Y; Zhu T; Ma C; Tao G (Journal of Pain Research)
Ruxin Gu, Ying Huang, Yin Li, Tong Zhu, Chao Ma, Gaojian Tao Department of Pain Medicine, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Gaojian Tao, Department of Pain Medicine, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, 210008, People’s Republic of China, Email dreamout@njglyy.comBackground: Chronic postoperative abdominal pain (CPAP) manifests as neuropathic or mixed pain, and conservative treatments often only provide temporary relief. This study evaluated the efficacy and safety of combining dorsal root ganglion pulsed radiofrequency (DRG-PRF) with scar radiofrequency ablation (RFA) for a better treatment.Methods: A total of 48 CPAP patients were divided into the scar RFA group (RFA group, n = 25) and the combination of DRG-PRF and scar RFA group (RFA+PRF group, n = 23). The visual analogue scale (VAS) and Globe Pain Scale (GPS) questionnaires were used for pain intensity and its effects before and at intervals of 1, 7, 30, 90 and 180 days after the procedure.Results: Baseline scores were comparable. The RFA+PRF group demonstrated significantly lower VAS scores at 1-day (1.2 ±  1.0 vs 1.6 ±  1.1, p = 0.040), 30-day (2.3 ±  1.1 vs 3.0 ±  0.9, p < 0.001), 90-day (2.7 ±  1.3 vs 3.7 ±  1.3, p < 0.001), 180-day of follow-up (2.7 ±  1.1 vs 3.5 ±  1.0, p = 0.002). GPS scores also showed significantly greater improvement in the RFA+PRF group at 30-day (51.2 ±  15.5 vs 62.2 ±  15.3, p = 0.028), 90-day (67.4 ±  16.3 vs 85.3 ±  14.7, p = 0.004), and 180-day (48.4 ±  13.3 vs 62.6 ±  10.9, p = 0.011) post-procedure. Additionally, a significantly higher proportion of patients in the RFA+PRF group achieved ≥ 50% pain relief at both 3 and 6 months (p < 0.05). No adverse reactions were observed in any participants.Conclusion: The combination of DRG-PRF and scar RFA has demonstrated significant efficacy and high safety in the treatment of CPAP. Compared to scar RFA alone, the combined therapy provides more durable and significant long-term pain relief, making it a better choice for pain management in CPAP patients.Keywords: chronic postoperative abdominal pain, dorsal root ganglion, pulsed radiofrequency